2014
DOI: 10.1016/j.jval.2014.08.2235
|View full text |Cite
|
Sign up to set email alerts
|

Economic Burden of Asthma in Vietnam: An Analysis from Patients' Perspective

Abstract: A627identify the direct costs, including costs for drugs and medical services, and indirect costs, including loss productivity, loss of work, cost for accommodation and transportation due to treatment and other costs of patient and caregivers. Results: Annual total cost per patient with asthma accounts for 6,618,682 VND, from which direct costs are 2.5 times more than indirect cost (4,738,682 vs 1,880,000 VND). The total cost of asthma has increased following the asthma severity with 4, 960,278; 8,098,156; 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Asthma is a major chronic disease among children and adults and remains a significant health problem in Vietnam. 1 – 3 The prevalence has been estimated at 3.9–5.6% of adults aged 21–70 years; 4 in Ho Chi Minh city (where this study was conducted), the prevalence of “ever asthma” in children aged 6–7 years was 10.9% and that of wheezing in children aged 13–14 years was 29.5%, the highest in the Asian-Pacific region. 5 The prevalence of asthma in Tien Giang, a rural province participating in this study, was 6%.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Asthma is a major chronic disease among children and adults and remains a significant health problem in Vietnam. 1 – 3 The prevalence has been estimated at 3.9–5.6% of adults aged 21–70 years; 4 in Ho Chi Minh city (where this study was conducted), the prevalence of “ever asthma” in children aged 6–7 years was 10.9% and that of wheezing in children aged 13–14 years was 29.5%, the highest in the Asian-Pacific region. 5 The prevalence of asthma in Tien Giang, a rural province participating in this study, was 6%.…”
Section: Introductionmentioning
confidence: 98%
“…The majority of the ambulatory care of asthma in Vietnam is provided by primary care physicians (PCPs); however, the use of controller medications (eg, inhaled corticosteroids [ICS]) in this setting is challenge because of their unavailability 11 and/or unaffordability for patients with a low/average income. 1 , 2 , 12 – 14 Apart from this, lack of knowledge on asthma management by health care providers is another factor contributed to this low level of asthma control. It has been shown that knowledge and competence of PCPs are low and vary among countries and with time in the same country, 15 – 19 but these could be improved by education.…”
Section: Introductionmentioning
confidence: 99%
“…Asthma is a major chronic disease among children and adults and remains a significant health problem in Vietnam. 1 – 3 The prevalence of asthma in Vietnam among adults aged 21–70 years has been estimated at 3.9%–5.6%. 4 In Ho Chi Minh city (where this study was conducted), the prevalence of “ever asthma” among 6–7 year olds was 10.9% and that of wheezing in children aged 13–14 years was 29.5%, the highest in the Asian-Pacific region.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Many reasons exist for this low level of asthma control, for example, related to the health care system and/or the doctor–patient relationship. Besides issues related to the health care system (e.g., unavailability of controllers, 10 unaffordability for some patients 1 , 2 , 11 – 13 ) or to physicians (e.g., incorrect diagnosis, lack of knowledge on asthma management, insufficient time or unwillingness to discuss matters with patients) 14 , 15 and patient-related problems (e.g., low level of treatment adherence), the patient’s low level of knowledge about the disease (particularly knowledge on self-management) is an important factor contributing to the low level of asthma control. 16 …”
Section: Introductionmentioning
confidence: 99%
“…In Vietnam, asthma remains a health and economic burden. The estimated prevalence among adults ranged from 2.4%-6.0% in 2011 and the total cost of asthma was 23,165 billion Vietnam Dong (VND) in 2014 [3][4][5][6] .According to the Global Initiative for Asthma (GINA), the important goals of asthma management are to gain good control of asthma symptoms and to minimize the risk of future asthma-related consequences 1 . Uncontrolled asthma is associated with many adverse outcomes, namely decreased lung function, increased risk of life-threatening asthma exacerbation, poor quality of life, and increased treatment cost 1 .…”
mentioning
confidence: 99%